Social self-efficacy mediates WeChat use and cross-cultural adaptation among international students in Chengdu, China - Kai, Zhang; Ting, Su Hie (Asian Scholars Network (ASNet), 2024)
Social media supports international students to become more integrated into the host culture during their adaptation and to maintain ties with people their home country. In China, WeChat has the social attributes to help international students to cope with academic and social challenges in the host society but it seems that personal self-confidence may affect sociocultural adjustment. The study examines the relationship between WeChat use, social selfefficacy and cross-cultural adaptation among international students in China. The preliminary study involved 24 international students in China who filled in an online questionnaire on cross-cultural exposure, WeChat usage, social self-efficacy and cross-cultural adaptation was formulated. The results showed frequent WeChat use, and it helped the respondents to learn Chinese language skills, make friends, and obtain social support to deal with study and life problems. They also reported positive attitudes towards their social skills and confidence in their host countries, but they were less confident when talking to strangers or expressing their opinions. Nevertheless, the respondents reported satisfactory cross-cultural adaptation because of the support from classmates, teachers, and the university. However, they were neutral on whether they have integrated into the culture in China, or felt capable talking to locals and making decisions. Our findings indicated that social self-efficacy exerts an indirect effect on the unidirectional link between social use of WeChat and cross-cultural adaptation.